Impact of Organizational Culture on Employee Performance - Kumari, Neeraj; Singh, Devi (Prabandhan: Indian Journal of Management, 2018)
Culture is made up of the values, beliefs, underlying assumptions, attitudes, and behaviors shared by a group of people. Culture is the behavior that results when a group arrives at a set of - generally unspoken and unwritten - rules for working together. The culture of a company as a whole might be weak and very difficult to characterize because there are so many subcultures. Each department or work cell may have its own culture. The aim of the study was to analyze the impact of work culture on the performance of the employees in a leading plastic manufacturer company. ExploratoryÂ research was used to gather preliminary information which helped in defining the problems and suggest hypotheses. The relationship between work culture and performance management system (PMS) was studied and the effect of the work culture on performance management system was found out to be 3.1%. Companies should conduct seminars and different activities to develop team spirit amongst employees. HR should ensure that the job description clearly defines KRA's and employees should be involved in the process of goal setting.